The Effect Reciprocal Teaching Strategy of Critical Thinking Skills in Learning Tematic Class V - Sundahry Sundahry; Yanti Fitria; Rakimahwati Rakimahwati (International Conferences on Educational, Social Sciences and Technology)
The purpose of this study was to investigate: the effect of reciprocal teaching strategies on the critical thinking skills of learners. This research is a quasi experimental type research. The population is all students in SD Nanggalo Tarusan Pesisir Selatan and the samples are students of VA and VB class as many as 50 people. This sampling technique is porpusive sampling. Data from the research results obtained from critical thinking skills tests. The results showed that the critical thinking skills of learners who were given a reciprocal teaching strategy were higher than conventional learning.